(untitled) (Journal of Atomic and Molecular Sciences, 2018)
We report a theoretical study of low-energy structures (LES) in the process of the strong-field ionization in the velocity gauge when considering non-dipole approximation and Coulomb corrections respectively. Comparisons have been made between considering non-dipole approximation and Coulomb corrections. A derivation of the photoelectron energy spectra for a hydrogen atom in a strong linearly polarized laser field is presented, which is considering non-dipole approximation and Coulomb corrections in the ground state. Based on the quantum and semiclassical analysis, we calculate ionization rates changed with the energy and variable regular changed with the wavelength and intensity have been also discussed.